Mathematical Fluid Mechanics, a Tribute to Giovanni Paolo Galdi - Carapau, Fernando (2012)
This International Conference is warmly dedicated to Professor Giovanni Paolo Galdi on the occasion of his 60th birthday. The conference will honor his many outstanding contributions to the broad field of Mathematical Fluid Mechanics, and the inspiration, generosity and dedication he has provided to his friends, colleagues ans students during his creative scientific career. The conference is an excellent opportunity to bring together world leaders in theoretical, numerical and experimental Fluid Mechanics, Professor Galdi´s friends and collaborators, to celebrate this research field, highlighting its achievements and giving new insights to open problems. Our aim is also to promove the interaction and the exchange of ideas with younger researchers, and to stimulate international collaboration. This volumw contains a collection of abstracts corresponding to the invited and contributed lectures that will be delived during the conference. We would like to welcome all the participants and, in particular the invited speakers, who have enthusiastically accepted our invitation to this special occasion, since the start of the project. The financial and organization support of the following institutions, which made this conference possible, are gratefully acknowledged: Fundação para a Ciência e a Tecnologia (FACC Program); Fundação Calouste Gulbenkian; Fundação Luso-Americana para o Desenvolvimento; CEMAT-Center for Mathematics and its Applications, Instituto Superior Técnico. Lisbon, May 21, 2007 Adélia Sequeira, Fernando Carapau, João Janela